Ar plasma-assisted P-doped Ni3S2 with S vacancies for efficient electrocatalytic water splitting. Issue 6 (4th February 2021) - Yang, Yaqian; Mao, Han; Ning, Rui; Zhao, Xu; Zheng, Xiaohang; Sui, Jiehe; Cai, Wei
Abstract : Doping engineering is considered an effective way to improve the electrocatalytic water splitting performance of catalysts. Abstract : Doping engineering is considered an effective way to improve the electrocatalytic water splitting performance of catalysts. In this paper, P-doped Ni3 S2 /NF was prepared by Ar plasma-assisted chemical vapor deposition, where the P dopant was efficiently introduced into Ni3 S2 /NF under the assistance of Ar plasma. Meanwhile, numerous vacancies were generated due to plasma bombardment. In the doping process, the P dopants replace the S vacancies, which contributes to the strong bonding between the P dopants and Ni3 S2 . Due to the synergistic effect of the P dopants and S vacancies, the Sv -Ni3 S2− x P x -4 catalyst has low HER and OER overpotentials of 89 mV and 216 mV at 10 mA cm −2, with a lower impedance value and good stability. The present work shows a facile route to introduce dopants and vacancies into catalyst materials for adding active sites, eventually improving their electrocatalytic performance.